Hubungan Panjang Stump Terhadap Tingkat Kemampuan Lokomotor Pada Pasien Pengguna Transfemoral Prosthesis - Nur Rachmat; Muhammad Syaifudin; Putri Utami Sulistyawati (Jurnal Keterapian Fisik, 2016)
Abstract : Amputation, Stump Length, Locomotor Ability, Transfemoral Prosthesis. Transfemoral amputation is an amputation that removes part of the femur (Coletta, 2000) Classification of transfemoral amputation, short stump transfemoral is leaving less than 35% of the length of the femur. In the medium stump transfemoral leaving between 35% - 60% of the length of the femur. Long stump transfemoral remains among more than 60% of the length of the femur(Coletta, 2000). Loss of some lower extremity on the human body causes incapacity (disability) person to perform variety of activities (Bachtiar, 2014), and led to the disruption of the locomotor abilities and functional abilities of the body of the patient. (Raichle, 2008). Longer stump can improve locomotor abilities of the patient. The population in this study all patients adaah transfemoral amputation who came to Kuspito Clinic at Karanganyar, with total of 49 patients in 2015. Use of purposive sampling technique to obtained a sample of 30 patients with transfemoral prosthesis. Independent Variabel which is used in this research is the length of the stump, While Dependent Variable in this research is locomotor ability of transfemoral prosthesis patients. Hypothesis test results show the value of probability (p-value) of 0.000 <α = 0,05 so that H0 rejected and H1 accepted, which means there is a long-stump against the patient's level of ability of the locomotor pda transfemoral prosthesis users with value of correlation (r) 0.718, the interpretation is strong correlation between variable.